Propuesta de fortalecimiento de la fiesta religiosa en honor a Santa Rosa de Lima del cantón Zapotillo de la provincia de Loja - González Zhinín, Ximena Del Cisne (2016)
The present “PROPOSAL FOR STRENGHTHEINING RELIGIOUS PARTY IN HONOR OF SANTA ROSA DE LIMA OF ZAPOTILLO CANTON OF LOJA PROVINCE” it is directed to the contribution at tourism development through of the consolidation of this celebration. The scope of this investigation work focuses on strengthening the religious festival in honor of St. Rose of Lima which is within the classification of intangible cultural heritage as the INPC. It aims to promote ad disseminate this religious festival to attract domestic and foreign tourism contributing to tourism development and economic partner of the canton and the southern region of the country and to preserve and maintain the customs and traditions. The Zapotilllo canton has an average altitude of 325 meters, the annual temperature ranges from 24 to 30º C. It has an area of 1238 km2, a population of 12063 inhabitants. Zapotillo is a diminutive of zapote fruit that is characteristic of the place, that was harvested in abundance; hence the first settlers took their name. The cantonal seat is Zapotillo, Spanish settlement founded by Sebastian de Benalcázar on January 10 of 1534. Your cantonización was the august 27 of 1980m during the presidency of Ab. Jaime Roldós Aguilera. The Zapotillo canton has an urban parish that bears his name, six rural parishes: Cazaderos, Paletillas, Garzareal, Limones, Bolaspamba and Mangahurco. The canton is dedicated to the production of corn, tomato, onion, rice, cassava, pumpkin, melon and raising poultry, cattle, pigs, horses and goats; this is their main source of production. The canton has the following educational institutions: one kindergarten, two primary schools and a school located in the regional town. It also has the Health Center Nº 13 Zapotillo, two Rural Health Places (PSR) in Cazaderos y Paletillas and two Health Places (PS) that are in Cazaderos. This canton is known for its tranquility, hospitality, varied an warm climate, has several natural attractions like: River Catamaayo-Chira, Cascada El Coronel, Reserva Natural de Bosque Seco La Ceiba, Río Chico o Alamoar, Cascada de Lobos, Cueva del Lagarto, Laguna La Lagartera, El Florecimiento de los Guayacanes, Bosque Seco Cerro Negro among others, we could also mention within cultural attractions, civic holidays like traditional cantonizacion commemorated 27 August of each year and religious festivals as of August 30 in honor of Santa Rosa de Lima. This begins on august 21 with the ninth in honor to the saint, the religious commitment, priostes, guests and devotees take part, culminating the same on August 29 with rosary and Eucharist eve party, August 30 principal feast day Mass is performed; the end of it with the sacred image on the shoulders of the devotees and assistants starts procession through the main districts of the Zapotillo parish. In the evening cultural events in which exalt the Holy and so ends the feast if St. Rose of Lima are made. The interviews, tabs MINTUR tourist inventories and summary, along with the information obtained from the field study support for canton and religious holidays, worked for execution and analysis of EFI and EFE matrices, the present work research, determined the importance of certin actions on the dissemination and promotion of the religious festival. The internet blog, the information brochure and video are reflected in the above results and analysis, thus achieving promotion and dissemination of culture, religious and party touristic of Santa Rosa de Lima and of the Zapotillo canton. It was carried out aimed at the trainer members of Committee GAD parties based on intangible cultural heritage, emphasized in importance cultural promotion of regions feast freeing space for a forum in which there were quotations, questions and conclusions about the topics discussed being a significant contribution for objectives project. Because of the cultural importance of religious holidays and the economic and social benefits they offer, it is concluded that it is feasible to implement the proposed of strengthening of that celebration using actions for dissemination and advocacy, contributing to the growth and development of tourism.